PERANAN DPRD DALAM PROSES PENYUSUNAN PERATURAN DAERAH DI KABUPATEN JOMBANG BERDASARKAN UNDANG-UNDANG NO. 23 TAHUN 2014 - Khotibul Umam; Kuswanto Kuswanto; Syaiful Bahri (Fakultas Hukum Universitas Darul Ulum, 2023)
One of the instruments in implementing local government is the DPRD which is a regional people's representative institution. The DPRD has a Legislative Function which is carried out with the Regional Head. The legislative function of the DPRD is the function of forming regional regulations with the regional head which must be guided by what has been stipulated in Law Number 23 of 2014 concerning the Establishment of Legislative Regulations. To carry out these functions DPRD members also have certain rights, one of which is the Right of Initiative as the right to submit draft regional regulations. Regional regulations are one of the important instruments in regional government where regional regulations regulate local content specific to regions that are not regulated in the law. In 2021 the Jombang Regency DPRD has high initiative rights. However, in 2022 - 2023 the use of the initiative rights of the Jombang Regency DPRD will decline drastically. The purpose of this study was to find out and analyze the implementation of the legislative function of the Jombang Regency DPRD. (1). What is the role of the legislative function of the Jombang district DPRD in 2022-2023, is there an initiative proposal from the DPRD? (2). What are the factors and obstacles in carrying out the legislative function of the proposed DPRD initiative? This research uses a library research type that examines various documents related to research. The method used by the author is a normative juridical writing method using a statute approach and a material approach using the DPRD's code of ethics. This research is limited by two research focuses, namely (1) what is the role of the legislative function of the Jombang Regency DPRD in 2022-2023, there are proposals for initiatives from the DPRD (2) what are the supporting and inhibiting factors in carrying out the legislative function of the DPRD initiative proposal? Furthermore, there are two legal materials used in this study, namely primary legal materials, secondary legal materials. The results of this study indicate that the formation of regional regulations includes four stages, consisting of; assessment stage, planning stage, discussion stage, and validation stage. From the results of the study it was also found that in the legislative function process the DPRD during 2022-2023 experienced a setback where the DPRD became increasingly passive. The right of initiative is reduced until it is not used at all. However, the process of implementing its legislative function has been carried out in accordance with the applicable laws and regulations. However, there are still obstacles that affect the legislative function of the DPRD, including inadequate human resources, delays in the process of establishing the RAPERDA, and lack of community involvement. Keywords: BAPEMPERDA, Regional Regulation, jombang district